Assessing public transport accessibility for people with physical disabilities in burgos, spain: A user-centered approach to inclusive urban mobility - Juan L. Elorduy; Yesica Pino; Ángel M. Gento (PLoS ONE, 2025)
Background Public transport accessibility is vital for fostering inclusive and sustainable urban development, ensuring equitable mobility for individuals with physical disabilities or reduced mobility. Globally, over 1.3 billion people, including 4.12 million in Spain, live with disabilities. Despite legislative progress, many cities fail to meet accessibility standards that guarantee safe and independent public transport use. Aim This study evaluates the accessibility of 431 bus stops in Burgos, Spain, using a methodological design that combines compliance with accessibility standards and the lived experiences of individuals with disabilities. By identifying critical barriers and opportunities for improvement, this research provides actionable insights for urban planners and policymakers, offering a replicable framework for cities facing similar challenges. Methods A validated and reproducible methodology was employed to evaluate accessibility conditions through in situ observations, including the geolocation of bus stops and photographic documentation. This approach guarantees a user-centred perspective through collaboration with local disability organisations. Results The analysis identified significant barriers, including inadequate vehicle encroachment prevention, poorly designed shelters, unsuitable stop locations, and limited accessible formats such as Braille and audio. These challenges hinder the independent use of public transport for individuals with disabilities or reduced mobility. Conclusions Addressing these barriers can substantially enhance urban mobility, reduce environmental impacts, and support Sustainable Development Goal 11, particularly Target 11.2. The proposed methodological design provides a practical framework for urban planners to create more inclusive, resilient, and sustainable transport systems globally.